Efforts of the Diniyah Takmiliyah Communication Forum in Increasing Interest in Reading the Qur'an - Eka Yuni Purwanti; Amir Mukminin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
Religious education material is an important aspect that must get priority in children's education because it is precisely with knowledge about religion that children will know the nature and purpose of their lives. Religion as a guide for humans to make humans as insanul kamil. Allah has sent down the book as a complement to the previous books, namely the Qur'an as the primary and first source of all Islamic teachings. The kindest heart is the heart that pays attention to the Qur'an, and the best house is the house in which the Qur'an is read, studied, studied, and practised in everyday life. This study uses qualitative research, data collection methods using interviews, observation, and documentation. At the same time, the data analysis is data reduction, data presentation, and conclusions. The results of this research are the efforts made by FKDT are Assisting Madrasah Diniyah Operational Permits or Madrasah Charters, holding PAI and Art Subject Contests (MAPSI) throughout Jatipurno District, Seeking Incentives for Madrasah Teachers, holding TPQ Management Technical Bimtek Socialization. The success of FKDT in increasing interest in reading the Qur'an is the completion of data collection on madrasas in Jeporo Village in collaboration with KUA, Contest (MAPSI), socialization of TPQ management guidance and counselling, seeking a spirit for Madrasah teachers, assisting with operational permits for madrasah diniyah or madrasa charter, as well as establish relations with related institutions.